Modernist Shepherdess: Gertrude Stein’s Pastoral Sounds - Amy WELLS (E-REA)
Investigating Gertrude Stein’s use of a pastoral countryside with war themes sheds light on her continuous mise en scène of the pastoral, and her production of pastoral sounds. In her own way, Gertrude becomes the modernist shepherdess of a mechanized pastoral soundscape. This study will demonstrate that buried within the difficult Steinese language, pastoral elements, such as those of specific sounds of cowbells, tinkling waterfalls, and birdsong or human song, help readers find their way along the narrative through its soundscape. To understand Stein’s pastoral sounds, we will first study her pastoral influences, then we will turn our attention to her pastoral productions, notably those involving pastoral sounds, in the works Four Saints in Three Acts; The World is Round; Paris France; and Wars I Have Seen. Ultimately, the pastoral sounds present in these texts invite the readers to join in a countryside afternoon promenade led by the shepherdess herself.